Effects of Single-Task Versus Dual-Task Training on Balance Performance in Elderly Patients With Knee Osteoarthritis - Aslıhan UZUNKULAOĞLU,; Duygu KERİM,; Saime AY,; Süreyya ERGİN, (Archives of Rheumatology, 2020)
Objectives: This study aims to compare the effects of single-task and dual-task training on balance performance in elderly patients with knee osteoarthritis (OA). Patients and methods: Fifty elderly osteoarthritic patients with balance impairment (16 males, 34 females; mean age 72.9±5.5 years; range 65 to 84 years) were included in this study. Patients were randomly assigned to single-task balance training (group 1) or dual-task balance training (group 2) groups. Balance activities were given to both groups for three times a week for four weeks. Patients in group 2 also performed cognitive tasks simultaneously with these exercises. Patients were evaluated with Berg balance scale (BBS), kinesthetic ability trainer static and dynamic scores, timed up and go (TUG) test and walking speed (WS) for single and dual tasks, number of stopping and activities-specific balance confidence (ABC) scale at baseline and at the end of four weeks. Results: At the end of the therapy, there were statistically significant improvements in BBS, KAT 2000 static and dynamic scores, TUG test and WS for single and dual tasks, number of stopping and ABC scale in both groups (p<0.05). But there was no statistical difference in any parameter between the groups (p>0.05). Conclusion: Both single- and dual-task trainings are effective in improving balance performance under single- and dual-task conditions in elderly patients with knee OA. Dual-task training is not superior to single-task training for balance improvement in elderly osteoarthritic patients.